Study on the hydrate formation region in a wellbore during Subsea Mudlift Drilling. (February 2021) - Wang, Xuerui; Hasan, AR; Zhang, Bo; ke, Ke; Wang, Yanhong; Zhang, Peng
Subsea Mudlift Drilling is a newly developed technology that provides a good solution to the problem of narrow pressure window in deep-water areas. However, current researches on Subsea Mudlift Drilling seldom focus on hydrate formation in a wellbore. Considering the shortcomings of current researches, a heat transfer model is established in this paper considering the specific flow path during Subsea Mudlift Drilling. A numerical model for the pressure profile during Subsea Mudlift Drilling is also established considering the lift force by the subsea pump. On basis of these models, a prediction method for the hydrate formation region is proposed, combining the hydrate phase equilibrium equation. In addition, a series of numerical simulations are conducted, which indicate that hydrate is easier to form during Subsea Mudlift Drilling than during conventional drilling. In order to reduce the hydrate formation region, a smaller head for the subsea pump, smaller diameter of the return line, larger displacement of the drilling fluid, and higher concentrations of inhibitors are suggested during Subsea Mudlift Drilling. On the basis of the numerical simulation results, an optimization method of hydraulic parameters for Subsea Mudlift Drilling is proposed. Conclusions and suggestions in this paper can help engineers to reduce hydrate formation during subsea Mudlift Drilling.